Pulmonary Thromboembolism Caused by Prolonged Compression at the Femoral Access Site and a Venous Aneurysm of the Ipsilateral Popliteal Vein - Arakawa, Kentaro (Ann Vasc Dis, 2016)
A 51-year-old female with dilated cardiomyopathy underwent a cardiac catheterization via right common femoral vein and artery. Prolonged compression with a bandage and extension of supine bed rest were needed. Immediately after standing up, she lost consciousness and developed electromechanical dissociation. The echocardiogram revealed a huge thrombus filling the main pulmonary trunk and massive enlargement of right ventricle, which suggested acute pulmonary thromboembolism (PTE). Images of computed tomography taken 2 months later detected a huge venous aneurysm of the right popliteal vein. Prolonged compression at the groin area might enhance blood stasis of the ipsilateral popliteal venous aneurysm, followed by life-threatening PTE.